THE ROLE OF THE FAMILY IN SOCIAL LIFE AND THE SOCIO-ECONOMIC AND PSYCHOLOGICAL PROBLEMS OF ONE-ONE FAMILIES - Xakimova Sarvinoz Sharifjon qizi (Scholars Digest Publishing, 2023)
This article shows more broadly the importance of the family in a person's life, as well as the need to provide economic and psychological support to single-parent families.
Keywords: Family, society, marriage, world experience, orphaned children, children left without parental care, social orphanage and implementation.